Constructive Alignment of the E-learning Course Introduction to Dairy Technology - Tranberg Andersen, Lene (Improving University Science Teaching and Learning, 2023)
In constructive alignment focus is on the coherence between intended learning outcomes (ILO) of the course, teaching learning activities (TLA) and assessment tasks (AT). Constructive aligned teaching is based on the hypothesis that students use the teaching learning activities to construct their knowledge or teaching outcomes. It is therefore important to actively use the ILOs and the TLAs to tell the students what they should learn and how they should lean it. The goal is to provide good teaching in a positive learning environment, through the use of constructive alignment to ensure increased learning outcomes and deeper learning (Biggs & Tang 2007).